CRIMINAL ACTION DATA INFORMATION SYSTEM AT THE POLICE OFFICE - Sulistiyanto Sulistiyanto; Reza Redo; Chen B Zhao; YJ Shin (Journal of Technology and Data Science, 2022)
The Indonesian National Police (POLRI) is a law enforcement security apparatus always readyto serve all people who need help and protection from all crimes. The Abung Semuli sector, located onJalan Semuli Raya, Abung Semuli District, North Lampung Regency, Indonesia, serves people who needassistance. Criminal data processing in the Abung Semuli sector has not yet used computer technologyas a tool. It is still recorded in the crime data book in processing criminal and civil data. Still stored ina form that makes it difficult to find data and make reports on criminal data. The proposed criminaldata information system functions to report the list of members, list of articles, and reports of criminalacts. In the process of searching for data and reports, it can produce accurate information.